Pengaruh Struktur Modal, Kebijakan Dividen dan Profitabilitas Terhadap Nilai Perusahaan: Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Berta Oktavia; Patmala; Nabila Anjelia; Nabilah Febiyanah; M. Rafi Albani; Yuli Nurhayati (Masyarakat Ekonomi Syariah Bogor, 2025)
This research is a literary study. which will discuss previous theories and research regarding the influence of capital structure, dividend policy and investment policy and profitability on company value. The method used is quantitative descriptive analysis where the data used is theory and calculations of capital structure, dividend policy, profitability and company value. The results of the research capital structure influences company value, overall that the influence of dividend policy has an influence on company value, overall that profitability affects company value, overall the results of 30 previous studies can be stated that the variables of capital structure, policy dividends and profitability have a mutual influence on company value